2015
DOI: 10.1002/app.42787
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet photopolymerization and performances of fast‐water absorbing sodium polyacrylate

Abstract: A kind of fast-water absorbing sodium polyacrylate was prepared by UV polymerization under no crosslinker or initiator condition. Influence of factors, such as exposure time, neutralization degree, polymerization temperature, and monomer concentration on the absorption rate of the resin, were investigated. Its pH sensitivity, average absorption rate in distilled water and saline under load were also studied, respectively. The obtained resin reached to considerably high absorption rate: 4.6 g/g min and 2.6 g/g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A series of super absorbent resins have been prepared by our research group via UV initiated polymerization using initiators and cross‐linkers over the years 28–30 . In previous studies, 31 it was found that the super absorbent resins prepared by UV photo polymerization without any cross‐linking agents and initiators had higher water absorption and salt resistance, however, the water absorption ability of each batch of resins fluctuated greatly. Therefore, the polymerization and crosslinking mechanisms and experimental conditions of this polymerization method needed to be further explored, which is of great significance to the future development of high‐performance superabsorbent hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…A series of super absorbent resins have been prepared by our research group via UV initiated polymerization using initiators and cross‐linkers over the years 28–30 . In previous studies, 31 it was found that the super absorbent resins prepared by UV photo polymerization without any cross‐linking agents and initiators had higher water absorption and salt resistance, however, the water absorption ability of each batch of resins fluctuated greatly. Therefore, the polymerization and crosslinking mechanisms and experimental conditions of this polymerization method needed to be further explored, which is of great significance to the future development of high‐performance superabsorbent hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the concentration of the fixed ions and sodium ions in the polymeric network gels increased because of the electrostatic interactions between the negatively charged anionic–nonionic surfactant and the positively charged sodium ions. According to Flory's theory, the high osmotic pressure is related to the high ionic concentration in polymeric network gels. The high osmotic pressure resulted in the rapid diffusion of water from the outside to the inside of the particles.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, on the basis of our previous work, the HPMC- g -PAA superabsorbent resin with multifunction of water absorption, water retention and biodegradability was successfully prepared, and the influences of the weight ratio of HPMC/AA, the amount of MBA, irgacure-2959 and urea and the neutralization degree on the properties of the material were studied, and the HPMC- g -PAA/urea composite with slow-release fertilizer was prepared on the optimized synthesis conditions. We anticipate that the combination of PAA and HPMC can enhance water absorbency, improve the functionality of controlled-release fertilizers, and enhance the biodegradability of synthesized superabsorbent polymers.…”
Section: Introductionmentioning
confidence: 99%